PKM PENINGKATAN POTENSI PEMASARAN EDI PRINT DI BALI - Tunjungsari, Hetty Karunia; Victoria Valentina (Jurnal Serina Abdimas, 2025)
This Community Servic program aims to enhance the marketing potential of Edi Print in Bali through a comprehensive strategy. The methods applied in this program include surveys, training, mentoring, and evaluation. The survey was conducted to identify the needs and challenges faced by Edi Print artisans in Bali. The training sessions focused on improving innovative design skills in line with market trends, utilizing digital marketing technologies, and developing a strong and recognizable brand. Mentoring was provided to assist artisans in implementing the marketing strategies they had learned. The results of the program show that Edi Print artisans in Bali face challenges such as a lack of innovative designs, limited access to digital marketing technology, and insufficient understanding of branding. Through training and mentoring, artisans were able to enhance their design skills, leverage social media for digital marketing, and build a stronger, more widely recognized brand. In conclusion, this program successfully improved the marketing potential of Edi Print in Bali. These improvements contributed to the development of new designs better suited to consumer preferences, enhanced digital marketing capabilities, and greater branding awareness, which helped their batik products gain market recognition. The implication of this program is that similar initiatives can be implemented in other regions to support the growth of local creative industries while expanding product reach. ABSTRAK Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan potensi pemasaran Edi Print di Bali melalui strategi yang komprehensif. Metode yang digunakan dalam kegiatan PKM ini meliputi survei, pelatihan, pendampingan, dan evaluasi. Survei dilakukan untuk mengidentifikasi kebutuhan dan tantangan yang dihadapi oleh perajin Edi Print di Bali. Pelatihan difokuskan pada peningkatan keterampilan desain yang inovatif dan sesuai dengan tren pasar, penggunaan teknologi pemasaran digital, dan pengembangan merek yang kuat dan dikenal di pasar. Pendampingan dilakukan untuk membantu perajin dalam mengimplementasikan strategi pemasaran yang telah dipelajari. Hasil PKM menunjukkan bahwa perajin Edi Print di Bali menghadapi tantangan dalam hal desain yang kurang inovatif, keterbatasan akses terhadap teknologi pemasaran digital, dan kurangnya pemahaman tentang branding. Melalui pelatihan dan pendampingan, perajin mampu meningkatkan keterampilan desain, memanfaatkan media sosial untuk pemasaran digital, juga membangun merek yang lebih kuat dan dikenal luas. Kesimpulan dari kegiatan PKM ini berhasil meningkatkan potensi pemasaran Edi Print di Bali. Peningkatan ini berkontribusi pada peningkatan desain-desain baru yang lebih sesuai dengan selera konsumen, kemampuan pemasaran digital, dan pemahaman branding yang membuat produk batik mereka dikenal di pasar. Implikasi dari PKM ini adalah bahwa program serupa dapat diterapkan di daerah lain untuk mendukung pengembangan industri kreatif lokal, sekaligus memperluas jangkauan produk.